Предмет: Алгебра,
автор: maudanyk
Помогите очень срочной!!! ПЕРЕОБРАЗОВАТЬ В ПРОИЗВЕДЕНИЕ
cos(α-π/6) · cos(α+π/6)
Ответы
Автор ответа:
0
cos(a-π/6)*cos(a+π/6)=1/2(cos(a-π/6-a-π/6)+cos(a-π/6+a+π/6))=
=1/2(cos(-π/3)+cos2a)=1/2*cosπ/3+1/2cos2a=1/2*1/2+1/2*cos2a=
=1/4+1/2*cos2a
=1/2(cos(-π/3)+cos2a)=1/2*cosπ/3+1/2cos2a=1/2*1/2+1/2*cos2a=
=1/4+1/2*cos2a
Похожие вопросы
Предмет: Математика,
автор: chiefktk
Предмет: Алгебра,
автор: kseniagavryshova
Предмет: Математика,
автор: mizernamargarita
Предмет: Математика,
автор: uli1066
Предмет: Русский язык,
автор: gulnara921213